Integrating Clinical Reasoning Principles in Case-Based Learning Sessions for First-Year Medical Students: Lessons Learned - Dinesh Kumar; Ramakrishnan Rajprasath; Magi Murugan (Tabriz University of Medical Sciences, 2019)
Background: Conventional pedagogies for case-based learning are designed with the intention of helping the student appreciate the relevance of content they learn and kindle their curiosity.However, these pedagogies embody certain shortcomings which inhibit them from reaching the intended objectives. The main aim of our initiative is to improve traditional case-based learning using the principles of clinical reasoning. Methods: A priori, two sessions were conducted in which two vignettes were administered to first-year medical students. We obtained the perceived acceptance which was equivalent to Kirkpatrick level 1 learning outcomes. Results: Overall outcomes were highly positive in terms of acceptability, fostering curiosity,increasing the relevance of learned content, and helping students learn to think in a logical way. Conclusion: With the increasing need for incorporating clinical reasoning skills in medical education, it is imperative that these skills are taught beginning with the preclinical years of medical education.